HEI SUSTAINABLE COMMUNICATION IN SOCIAL MEDIA: E-COURSE EVALUATION VIA TRIANGULATION METHOD - Ahrens, Andreas; Zascerinska, Jelena; Huliaieva, Liudmyla; Duranowski, Wojciech; Dąbrowski, Zbigniew; Santos, Margarida; Oliveira, Ana; Rodrigues, Timóteo; Oliinyk, Andrii (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Given that sustainable communication is already a complex phenomenon, the role of social media, currently growing rapidly, is underestimated by universities and academia. The present research aims at analysing the e-course “The power of social media in the professional development of teachers: personal brand, tools for educational products, promotion of sustainable development values” for HEIs teaching staff. The exploratory research was leveraged in this work for the e-course construction and evaluation. The exploratory empirical study was implemented in 2022-2023. The empirical study was built on the triangulation method referred to data collection and data analysis. The sample was composed by six trainers, 15 participants, and two experts. HEIs sustainable communication in social media is beneficial for all the involved as it supports just green transition, e.g. by lowering the carbon emissions by, for example, commuters, aimed at reducing climate impact and mitigating climate change. The empirical study allows drawing a conclusion that the e-course “The power of social media in the professional development of teachers: personal brand, tools for educational products, promotion of sustainable development values” for HEIs teaching staff was positively evaluated. The positive evaluation proposes that the e-course is effective and efficient.